Evaluation of Marginal Adaptation and Microleakage of Three Glass Ionomer-Based Class V Restorations: In Vitro Study - Ebaya, Maha M.; Ali, Ashraf I.; Mahmoud, Salah H. (European Journal of Dentistry, 2019)
Objective The aim of this study was to evaluate and compare the marginal adaptation and microleakage of class V cavities restored with conventional glass ionomer cement (GIC), resin-modified glass ionomer (RMGI), and bioactive ionic resin (BIR) restorative materials after 6 months of water storage.Materials and Methods One hundred twenty standardized class V cavities (2 mm deep, 4 mm in width, and 3 mm in height) were prepared in sound extracted human molar teeth, where the coronal margins were in enamel while the cervical margins were in dentin. Three glass ionomer-based restorations were tested (n = 40): GIC (Equia Fil), RMGI (Fuji II LC), and BIR (ACTIVA Bioactive Restorative). Half of the teeth from each group (n = 20) were evaluated for their marginal adaptation with scanning electron microscopy and the other half submitted to dye penetration test to examine microleakage. Further division for each subgroup (n = 10) occurred to be tested immediately, while the remaining teeth were examined after keeping for 6 months and thermocycling.Statistical analysis The outcomes were analyzed by Kruskal–Wallis and Mann–Whitney U tests.Results No statistically significant differences were observed among the three studied restorative materials. However, the differences were statistically significant in microleakage test between enamel and dentin and after water aging.Conclusion All tested restorative materials exhibited the same marginal adaptation and microleakage. Dentin substrate revealed greater microleakage than enamel, especially with BIR restorative material. Water aging had a negative effect on RMGI with respect to microleakage.
Keywords: glass ionomer; scanning electron microscopy; resin-modified glass ionomer; microleakage